Maternal Gestational Weight Gain in Relation to Antidepressant Continuation in Pregnancy - Wartko, Paige D.; Weiss, Noel S.; Enquobahrie, Daniel A.; Chan, Kwun Chuen Gary; Stephenson-Famy, Alyssa; Mueller, Beth A.; Dublin, Sascha (American Journal of Perinatology, 2020)
Objective Both excessive and inadequate gestational weight gain (GWG) are associated with adverse health outcomes for the woman and her child. Antidepressant use in pregnancy could affect GWG, based on evidence in nonpregnant women that some antidepressants may cause weight gain and others weight loss. Previous studies of antidepressant use and GWG were small with limited ability to account for confounding, including by maternal mental health status and severity. We assessed the association of antidepressant continuation in pregnancy with GWG among women using antidepressants before pregnancy.Study Design Our retrospective cohort study included singleton livebirths from 2001 to 2014 within Kaiser Permanente Washington, an integrated health care system. Data were obtained from electronic health records and linked Washington State birth records. Among women with ≥1 antidepressant fill within 6 months before pregnancy, women who filled an antidepressant during pregnancy were considered “continuers;” women without a fill were “discontinuers.” We calculated mean differences in GWG and relative risks (RR) of inadequate and excessive weight gain based on Institute of Medicine guidelines. Using inverse probability of treatment weighting with generalized estimating equations, we addressed differences in maternal characteristics, including mental health conditions.Results Among the 2,887 births, 1,689 (59%) were to women who continued antidepressants in pregnancy and 1,198 (42%) were to discontinuers. After accounting for confounding, continuers had similar weight gain to those who discontinued (mean difference: 1.3 lbs, 95% confidence interval [CI]: −0.1 to 2.8 lbs) and similar risks of inadequate and excessive GWG (RR: 0.95, 95% CI: 0.80–1.14 and RR: 1.06, 95% CI: 0.98–1.14, respectively). Findings were comparable for specific antidepressants and trimesters of exposure.Conclusion We did not find evidence that continuation of antidepressants in pregnancy led to differences in GWG.Key Points
Keywords: antidepressants; pregnancy; gestational weight gain; inadequate gestational weight gain; excessive gestational weight gain; adequacy of gestational weight gain